2021
DOI: 10.1002/bies.202100079
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic poleward flux: Finding balance between microtubule dynamics and sliding

Abstract: Continuous poleward motion of microtubules in metazoan mitotic spindles has been fascinating generations of cell biologists over the last several decades. In human cells, this so-called poleward flux was recently shown to be driven by the coordinated action of four mitotic kinesins. The sliding activities of kinesin-5/EG5 and kinesin-12/KIF15 are sequentially supported by kinesin-7/CENP-E at kinetochores and kinesin-4/KIF4A on chromosome arms, with the individual contributions peaking during prometaphase and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 154 publications
(266 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the increased spindle size and the increase resistance of the spindle MTs to cold-induced depolymerization in TTLL11-silenced cells all indicate that the spindle MTs are partially stabilized in these cells. Although the mechanism driving the spindle flux is still not fully understood it involves a fine balance between microtubule sliding and dynamics 37 , 38 , the reduced speed of the spindle flux in TTLL11-silenced cells is also compatible with a reduced dynamics of the spindle MTs. Previous studies showed that a slight stabilization of the spindle MTs leads to chromosome segregation errors 6 , 9 , 10 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the increased spindle size and the increase resistance of the spindle MTs to cold-induced depolymerization in TTLL11-silenced cells all indicate that the spindle MTs are partially stabilized in these cells. Although the mechanism driving the spindle flux is still not fully understood it involves a fine balance between microtubule sliding and dynamics 37 , 38 , the reduced speed of the spindle flux in TTLL11-silenced cells is also compatible with a reduced dynamics of the spindle MTs. Previous studies showed that a slight stabilization of the spindle MTs leads to chromosome segregation errors 6 , 9 , 10 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In cells, a lot of active kinesin motors, passive cross-linkers and other proteins are involved in the spindle elongation during anaphase. , , After the start of anaphase B, the MT depolymerase activity at the minus ends of MTs, where the spindle poles are connected, is switched off, while the MT polymerization at the plus ends of MTs is still on. ,,, The kinesin motors, such as kinesin-5 Eg5 motors, which provide the force to drive the spindle elongation, are working near the “unloaded regime” during the process . Here, we consider N MT pairs of antiparallel MTs to study the spindle elongation, as schematically shown in Figure a.…”
Section: Methodsmentioning
confidence: 99%
“…9,14 −16,21−23 polymerization at the plus ends of MTs is still on. 35,36,57,58 The kinesin motors, such as kinesin-5 Eg5 motors, which provide the force to drive the spindle elongation, are working near the "unloaded regime" during the process. 57 Here, we consider N MT pairs of antiparallel MTs to study the spindle elongation, as schematically shown in Figure 1a.…”
Section: Simplified Model Of Spindle Elongation Bymentioning
confidence: 99%
“…Chromosome misalignment induced by CENP-E depletion is accompanied by mitotic spindle assembly defects, mitotic catastrophe, and severe spindle positioning defects (Tame et al, 2016;Iegiani et al, 2021;Owa and Dynlacht, 2021). In addition, CENP-E is related to microtubule flux in early mitosis, which is required for the conversion from lateral to end-on attachment and chromosome congression (Shrestha and Draviam, 2013;Barisic and Rajendraprasad, 2021) (Figure 2). Kinesin-7 CENP-E is essential for kinetochore-microtubule attachment, chromosome alignment, and spindle assembly checkpoint in cell division.…”
Section: Functions and Mechanisms Of Kinesin-7 Cenp-e In Cell Divisionmentioning
confidence: 99%
“…CENP-E inhibition results in large chromosomes more vulnerable to defects in chromosome congression (Tovini and McClelland, 2019). CENP-E cooperates with chromokinesin KID and KIF4A to transport chromosomes toward the spindle equator along microtubules (Kapoor et al, 2006;Barisic and Rajendraprasad, 2021). The lateral kinetochoremicrotubule attachment is mediated by CENP-E and dynein, which is required for chromosome congression (Maiato et al, 2017).…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 99%